2017
DOI: 10.1097/nmd.0000000000000744
|View full text |Cite
|
Sign up to set email alerts
|

Self-Harm, Affective Traits, and Psychosocial Functioning in Adults With Depressive and Bipolar Disorders

Abstract: Self-harm refers to the purposeful destruction of bodily tissue without suicidal intention and for purposes that are not socially sanctioned. Little is known about the associations between a history of self-harm, mood symptoms, and functioning in adults with different types of mood disorders. Lifetime histories of self-harm, current mood symptoms, global functioning, and affective traits were collected on 142 adults with mood disorders. The prevalence of lifetime self-harm was higher in patients with bipolar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 30 publications
(24 reference statements)
2
24
2
7
Order By: Relevance
“…In the present study, our results of prevalence of NSSI was 62.2%, which was slightly lower than the prevalence of NSSI (77%) in a Canadian study among clinical populations (Preyde et al, 2014). Equally, Weintraub et al(Weintraub et al, 2017) found that about 37% of patients with depression and 52% of patients with bipolar disorder had at least one NSSI, which was also higher than the results of this study (34.3% and 27.9%, respectively). The discrepancies in estimates of the prevalence of NSSI may be relate to different sample sources and numbers, various assessment tools, wording of instructions, time frame for raising questions and data collection procedures.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…In the present study, our results of prevalence of NSSI was 62.2%, which was slightly lower than the prevalence of NSSI (77%) in a Canadian study among clinical populations (Preyde et al, 2014). Equally, Weintraub et al(Weintraub et al, 2017) found that about 37% of patients with depression and 52% of patients with bipolar disorder had at least one NSSI, which was also higher than the results of this study (34.3% and 27.9%, respectively). The discrepancies in estimates of the prevalence of NSSI may be relate to different sample sources and numbers, various assessment tools, wording of instructions, time frame for raising questions and data collection procedures.…”
Section: Discussioncontrasting
confidence: 87%
“…As a coping strategy for maladaptive individuals (Guerreiro et al, 2013), NSSI are more prone to be seen in clinical populations, especially in patients with depression or bipolar disorder who have poor ability of emotional regulation and coping (Kim et al, 2015). A recent study (Weintraub et al, 2017) observed that about 52% and 37% of patients with bipolar disorder and depression had NSSI at least once, respectively. Chinese researcher also found that 59 out of 153 Chinese patients with depression (38.6%) had committed NSSI in the past year (Fang and Li, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 61 These factors have also been observed in patients with BD. Impaired executive function, particularly impaired decision making and impulsivity, 62 66 has been linked to an increased risk of suicidal and NSSI behaviour. Similar observations have been made in patients with ADHD.…”
Section: Discussionmentioning
confidence: 99%